Designing a Secure Software-Defined Radio Transceiver using the Logistic Map (Journal of Engineering, 2021)
The need to exchange large amounts of real-time data is constantly increasing in wireless communication. While traditional radio transceivers are not cost-effective and their components should be integrated, software-defined radio (SDR) ones have opened up a new class of wireless technologies with high security.  This study aims to design an  SDR  transceiver was built using one type of modulation, which is 16 QAM, and adding a  security subsystem using one type of chaos map, which is a  logistic map, because it is a very simple nonlinear dynamical equations that generate a random key and  EXCLUSIVE  OR with the originally transmitted data to protect data through the transmission. At the receiver, the data will be recovered  using the same key, the received data is the same at the sender, so this result shows that the transceiver work normally and calculates the BER at the end each time the SNR changed. Our results indicate that the designed transmitter and receiver perform as usual and finally calculate the bit error rate when the signal to noise ratio is changed. The evaluation of BER indicates that simulated values are smaller than theoretical ones obtained using the BER tool. when SNR is equivalent to 7 dB, the theoretical and simulated BER obtained is 0.01695 and 0.00199, respectively. Designing soft defined radio transceiver using MATLAB  R  2011a  and system generator ISE14.1/SIMULINK.